2013
DOI: 10.1121/1.4824120
|View full text |Cite
|
Sign up to set email alerts
|

Clarity in communication: “Clear” speech authenticity and lexical neighborhood density effects in speech production and perception

Abstract: Speech produced in the context of real or imagined communicative difficulties is characterized by hyperarticulation. Phonological neighborhood density (ND) conditions similar patterns in production: Words with many neighbors are hyperarticulated relative to words with fewer; Hi ND words also show greater coarticulation than Lo ND words [e.g., Scarborough, R. (2012). "Lexical similarity and speech production: Neighborhoods for nonwords," Lingua 122(2), 164-176]. Coarticulatory properties of "clear speech" are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 43 publications
6
66
0
2
Order By: Relevance
“…Although these effects might seem contrary to the increased coarticulation in IDS (Andruski and Kuhl 1996), and in later-acquired words in IDS in particular (in the current study), they could in fact be interpreted as having a similar goal: to provide better information about the segments in a word. More extreme vowel articulation and more canonical consonant allophones straightforwardly provide better information about the identity of these segments; increased (consonant-to-vowel) coarticulation provides temporally-distributed and predictive information about the identity of the upcoming consonant (e.g., Ali et al 1971;Lahiri and MarslenWilson 1991;Beddor et al 2013;Scarborough and Zellou 2013). Thus, the confluent increase in degree of contextual nasalization (from consonant to vowel) and more extreme vowel articulation in ostensibly harder, later-acquired words in IDS are not incompatible and may even serve a similar purpose.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although these effects might seem contrary to the increased coarticulation in IDS (Andruski and Kuhl 1996), and in later-acquired words in IDS in particular (in the current study), they could in fact be interpreted as having a similar goal: to provide better information about the segments in a word. More extreme vowel articulation and more canonical consonant allophones straightforwardly provide better information about the identity of these segments; increased (consonant-to-vowel) coarticulation provides temporally-distributed and predictive information about the identity of the upcoming consonant (e.g., Ali et al 1971;Lahiri and MarslenWilson 1991;Beddor et al 2013;Scarborough and Zellou 2013). Thus, the confluent increase in degree of contextual nasalization (from consonant to vowel) and more extreme vowel articulation in ostensibly harder, later-acquired words in IDS are not incompatible and may even serve a similar purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Recall that prior studies have found evidence of consistent ND effects on hyperarticulation and coarticulation in laboratory speech, elicited as standard citation form speech or as explicitly (adult) listener-directed (e.g., Wright 2003;Munson and Solomon 2004;Scarborough 2013;Scarborough and Zellou 2013).…”
Section: Interim Discussionmentioning
confidence: 99%
See 3 more Smart Citations